PERAN POLRI DALAM MENANGANI LAPORAN DUGAAN PENYALAHGUNAAN WEWENANG DALAM TINDAK PIDANA KORUPSI SETELAH DITETAPKANNYA UNDANG-UNDANG NO 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Bayu Dewanto; Sri Endah Wahyuningsih (Jurnal Hukum Khaira Ummah, 2019)
The background of this research is Law number 30 of 2014 Section 20 states that if the result of Supervision of Government Internal Apparatus (APIP) in the form of administrative error, follow up in the form of administrative improvement, if there are administrative errors that cause loss of state finance done financial loss state and state losses are imposed on the Governing Body, if an administrative error occurs not due to an element of abuse of Authority. This is certainly contrary to the law of corruption. The issues raised in this study are how the role of the Police and the obstacles in handling reports of alleged abuse of authority in corruption after the enactment of Law No. 30 of 2014 on Government Administration, as well as what steps are needed for the handling of corruption can effectively prevent loss of state finances. This research uses qualitative method with empirical juridical approach. The results of the research indicate that the role of the Police in handling the report of alleged misuse of authority in corruption crime after the enactment of Law No.30 of 2014 is in handling the report of alleged abuse of authority, it is first the Police consult with experts, general experts, social experts and politics whether abuse of authority is included in the criminal realm or administrative error domain. In addition it is suggested to put forward on the results of supervision of APIP. Polri's obstacles in handling reports of alleged abuse of authority are: a) investigation of alleged misuse of authority done by APIP, b). No involuntary summons c) If there are administrative errors that incur losses of state finances, subsequent reversals are made to the state's financial loss so it can not be criminalized. Measures necessary for the handling of criminal acts of corruption can effectively prevent financial losses of the state a) Police cooperate and / or coordinate with BPK, KPK, PPATK, and other government agencies in law enforcement efforts and state financial loss returns; b) corruption prevention and prevention is actualized in the form of strategies to minimize the four aspects of the causes of corruption. The strategy includes preventive, detective and repressive aspects, which are carried out intensively and continuously. Keywords: Polri, Abuse of Authority, Corruption,